COMMUNICATION OF POLITICIANS WITH THE AUDIENCE: TOOLS AND SPECIFIC APPLICATIONS - Honcharenko, Maksym (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2022)
The process and mechanisms of communication between the politician and the audience, the role of external and conjunctural factors, their influence on the effectiveness of communication and the expediency of using certain means of interaction are studied. Factors that directly affect the quality of a political actor’s contact with voters are considered, as well as those that indirectly affect the relevance of political statements. Formulated principles of evaluating the effectiveness of communication with a certain audience. Actual problems of communication between the politician and the audience in the scientific, social, public and political spheres are revealed. The problem of communication between a politician and an audience is actualized in the scientific, socio-political, public, purely political spheres. The effectiveness and expediency of using certain formats of communication between a politician and an audience against the background of various external conditions is analyzed. Attention is focused on the need for careful analysis not only of the audience as such, but also of external factors that can affect the perception of information by the voter. The study of individual formats and the specifics of their application in communication between a politician and an audience opens up opportunities for more effective and transparent interaction between political actors and civil society. This enables the creation, improvement and effective use of the most appropriate means of public communication. Recommendations are provided for preparing, editing and evaluating the effectiveness of public communication activities in the context of political activity. It is proved that there is a connection between the effectiveness of a certain means of communication and external factors. Methods of assessing the expediency of using various means of public communication are proposed and attention is focused on their specificity. A hypothesis is proposed about the significant influence of external factors on the perception of information by the audience, in particular on the political behavior of voters.